A Study on the Electric Surface Potential and Hydrophobicity of Quartz Particles in the Presence of Hexyl Amine Cellulose Nanocrystals and Their Correlation to Flotation - Hartmann, Robert; Serna-Guerrero, Rodrigo (Frontiers in Materials, 2020)
In this work, the study of hexyl amine cellulose nanocrystal (HAC) as a renewable and environmentally-friendly reagent for the flotation of quartz (QRZ) is expanded with a focus on the changes of electrical states at the solid-liquid interface, the range of solid-gas interactions, and their impact on flotation operations under a turbulent regime. Furthermore, particle-bubble attachment probabilities were measured with the recently engineered automated contact timer apparatus (ACTA), a versatile technique used to deduce the wettability of microparticles and potentially predict their floatability. Therefore, the findings of the ACTA proved that, with sufficiently hydrophobic QRZ (i.e., HAC concentration ≥ 0.667 mgHAC/m2QRZ), stable particle-bubble attachments occur at particle-bubble distances in the range of tens of micrometres. The distances for the successful attachment of HAC-coated QRZ particles exceed the range of interactions reported in literature so far and imply the existence of structural or hydrodynamic phenomena acting between particle and bubble surfaces. The occurrence of so-called non-compressive particle-bubble attachments is shown to correlate with a significant increase in the floatability of QRZ, where recoveries up to 90% were obtained. Based on the experimental results, some insights on the nature of the long-range interactions responsible for the particle-bubble attachment of hydrophobic particles are provided.